Dakwah Pengentasan Kemiskinan dalam Pendekatan Teori David ,Mc.Clelland - Husen Saeful Anwar (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2011)
The concept of poverty reduction, as a religious doctrine (kâdal fakru an yakûna kufron), that has become a main agenda of da’wah, is not easy to implement so long as the mental attitude of poor people does not allow them to change. In line with this, the main strategy of a da’I has to be that of changing such mental attitude. Mc.Clelland, a development psychologist, provides an operational framework of strategy trough his concept the so-called N-Ach (Need for Achievement). Based on his theory, people would be progressive and prosperous only when they have N-Ach. Man with N-Ach, have strong drive for progress and achievement; be own creativity and innovation, and have strong will to improve his level to better condition. Da’wah can use this theory as a solution to poverty problems.